Noise thermometry at ultra low temperatures - Rothfuß, Daniel Simon; Reiser, Andreas; Fleischmann, Andreas; Enss, Christian (Applied physics letters, 2013)
We present a contact free cross-correlation noise thermometer experimentally characterized for temperatures between 0.8 K and 45 μK. The noise source is a cold-worked copper cylinder. The fluctuations of magnetic fields due to the thermal motion of the electrons in the copper cylinder are simultaneously monitored by two superconducting quantum interference device magnetometers. A subsequent cross-correlation of both channels reduces the noise contribution of the amplifiers by more than one order of magnitude. This technique covers almost five orders of magnitude in temperature including ultra low temperatures, which were accessible only by platinum nuclear magnetic resonance thermometers so far.
Gesehen am 21.01.2022